Media Crisis Management in the Algeria-Egypt 2010 Match: An Analytical Reading by Al-Shorouk Daily and Al-Masry Al-Youm - mehri, chafika (sports creativity, 2025)
the sports media Became the more types of media specialist attractive to the masses , its have ability to mobilization of public opinion ،The sport media has become a mirror reflecting the reality of events and sport problems , there appeared what is known Sports media crises, which aims to manage the crisis of media in the media coverage of the sports crisis ، wich its know many distractions and disruptions that could boasting public opinion , we have tried through this presentation to highlight the most important sporting media crisis in the Arab world in the twenty-first century ,” crisis between Algeria football match in Egypt Omdurman 2009” Through this theory study we search the concepts of sports media , management crisis communication crises in various stages of the crisis ،and the most barriers in media crises , in the analytical study we choose two samples of the most important newspapers contributed to the coverage of sports crisis "el chorouk Algerian newspaper, and the Egyptian today newspaper. How were the functions of the sports media in light of this crisis? what are the most important values contained in this crisis?, and how has the process of managing the crisis through journalist media ?. The key word :sport media ,crisis managemant,crisis communication